An In vivo Metabolic Reaction-Based Mass Difference Screening Strategy for Comprehensive Metabolite Profiling of the Huangqi-Danshen Herb Pair Using Ultra-High-Performance Liquid Chromatography Coupled with Quadrupole-Time-of-Flight Mass Spectrometry - Chen-Xi Liu; Xin-Lu Li; Cai-Yi Ma; Meng Ding; Ping Li; Hua Yang (World Journal of Traditional Chinese Medicine)
Objective: The absorbed prototypes and metabolites of traditional Chinese medicines in vivo are crucial for identifying their biological functions. However, comprehensive profiling of constituents in vivo is difficult owing to endogenous interference and low metabolite abundance. Therefore, a systematic strategy was proposed for screening and profiling exogenous components in biological matrices based on the mass differences between prototypes and the products of their metabolic reactions. Materials and Methods: Two hundred and forty-seven previously reported metabolic reactions were collected from the relevant literature on the Huangqi-Danshen (HD) herb pair, and a metabolic reaction-based mass difference database was created. The preprocessed data from experimental MS1 based on ultra-high-performance liquid chromatography coupled with quadrupole-time-of-flight mass spectrometry were automatically calculated mass differences by R programming and matched with the database to screen potential constituents. Finally, the components were annotated across the MS2 data. Results: A total of 164 components were annotated in the plasma samples from the rats after oral administration of HD, of which 20 were confirmed using the reference standards. The major metabolic pathways include methylation, dehydration, cysteine S-binding, glucuronidation, sulfation, and multistep reactions. Conclusions: This study revealed the metabolic characteristics and biotransformation regulation of HD and laid the foundation for elucidating its therapeutic effects. The proposed approach provides advantageous resources for evaluating the metabolites in the complex systems.